Strategi Guru dalam Menghadapi Perbedaan Kemampuan Siswa pada Pembelajaran IPAS di Kelas VI SD Negeri Sempol 2 Maospati - Arsanda Wikan Dinata; Izzatunnisa Alyya Attaqiya; Shalsabylla Alfarezma; Muhammad Imaduddin; Arif Mahya Fanny (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the teacher’s strategies in dealing with differences in students’ abilities in Science and Social Studies (IPAS) learning in Grade VI at SD Negeri Sempol 2 Maospati. Differences in students’ learning abilities become a challenge for teachers in creating effective and inclusive learning environments. This research used a descriptive qualitative approach. Data were collected through semi-structured interviews and documentation studies. The data analysis process was carried out through data reduction, data presentation, and conclusion drawing. The results showed that the teacher implemented a routine question and answer strategy before lessons began and before students went home to identify students’ understanding and increase learning motivation. The teacher also utilized audiovisual media such as YouTube learning videos, smart TVs, and projectors to help students understand IPAS materials more concretely and attractively. In addressing differences in students’ abilities, the teacher adjusted the level of questions according to students’ understanding and provided additional guidance through assignments and communication with parents. In addition, the teacher applied an assessment system that not only focused on test results but also appreciated students’ participation and learning processes. These strategies were considered effective in improving students’ motivation, discipline, confidence, and understanding of learning materials. The findings indicate that consistent and adaptive learn.